MODERN METHODS OF DEVELOPING FLUENCY IN YOUNGER STUDENTS - Yakubov Zafar Kudratovich (Scholar Express Journal, 2025)
This paper explores contemporary strategies employed to develop fluency in younger students, particularly in reading, writing, and oral communication. The integration of digital tools, differentiated instruction, and engaging pedagogies has revolutionized language fluency education. The study draws on current research and classroom practices to highlight effective methods and their impact on early learners
Keywords: Fluency; Early Childhood Education; Literacy Development